Consensus guidelines for diagnosis, prophylaxis and management of Pneumocystis jirovecii pneumonia in patients with haematological and solid malignancies, 2014. Issue 12 (December 2014) - Cooley, L.; Dendle, C.; Wolf, J.; Teh, B. W.; Chen, S. C.; Boutlis, C.; Thursky, K. A.
Abstract P neumocystis jirovecii infection (PJP) is a common cause of pneumonia in patients with cancer‐related immunosuppression. There are well‐defined patients who are at risk of PJP due to the status of their underlying malignancy, treatment‐related immunosuppression and/or concomitant use of corticosteroids. Prophylaxis is highly effective and should be given to all patients at moderate to high risk of PJP. Trimethoprim‐sulfamethoxazole is the drug of choice for prophylaxis and treatment, although several alternative agents are available.